A national analysis of the medical schools of training for merit award-winning laboratory medical doctors working in Britain - S. Steele; G. Andrade (BMC Medical Education, 2023)
Abstract Aims To inform the discussion regarding the origins of Laboratory Medical Consultant clinical merit award holders (LMC) whether the awards came from the Clinical Excellence Awards (CEA) or Distinction Awards (DA) schemes. Methods Setting - CEA is a scheme to financially reward senior doctors in England and Wales who are assessed to be working over and above the standard expected of their role. The DA scheme is the parallel and equivalent scheme in Scotland. Participants - All of the merit award holders in the 2019 round. Design - This involved a secondary analysis of the complete 2019 published dataset of award winners. Statistical analyses were performed with Chi-square tests set at p < 0.05 level for statistical significance. Results The top five medical schools (London University, Glasgow, Edinburgh, Aberdeen and Oxford) were responsible for 68.4% of the LMC merit award holders in the 2019 round. 97.9% of the LMC merit award holders were from European medical schools, whereas 90.9% of the non-LMC award holders were from European medical schools. The LMCs with A plus or platinum awards came from only six medical schools: Aberdeen, Edinburgh, London University, Oxford, Sheffield and Southampton. In contrast, the B or silver/bronze LMC award holders came from a more diverse background of 13 medical schools. Conclusions The majority of LMC merit award holders originated from only five university medical schools. All the LMCs with A plus or platinum awards came from only six university medical schools. There is an apparent overrepresentation of a small number of medical schools of origin amongst those LMCs that hold national merit awards.